PENGARUH UKURAN PERUSAHAAN, RASIO AKTIVITAS, DAN PROFITABILITAS TERHADAP PEMBAYARAN DIVIDEN PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Chandra, Haryani (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2019)
Ability of a company to provide consistent returns in the form of dividends can be a signal that the company has great operational activities so that it becomes attractive to investors. Dividend payments can be influenced by various factors, including company size, activity ratio, and profitability. This study aims to determine wheter company size, activity ratio, and profitability have an influence on dividend payments on cigarette companies listed in the Indonesia Stock Exchange. Independent variables in this study are company size, activity ratio, and profitability while dependent variable is dividend payments. The research method used is regression analysis by first conducting classic assumption tests. The results showed that company size, activity ratio, and profitability simultaneously have impact to dividend payments. Partially, company size and activity ratio has a significant influence on dividend payments while profitability has no significance influence on dividend payments.